Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Melalui Aplikasi Online Single Submission (OSS) di Desa Ngrimbi, Kecamatan Bareng - Kevin Nugraha Ramadhan; Mu’tassim Billah; Raden Muhammad Rusydan; Farah Farah; M.Ghifari Akmal Prayogo; Dwi Rafly Wibowo (Jurnal of Management and Social Sciences, 2023)
Legality has an important role for the progress of the business owned by all business actors, because legality is basically a form of granting permits granted by the authorities to every business actor in running their business. Legality itself is said to be important because it is used as evidence that the business being run or established is feasible and ongoing. People who do not understand the importance of business legality are a problem that causes many business actors who do not have business legality to support their business. The community service carried out by Group 10 KKN-T MBKM UPN "Veteran" East Java aims to sensitize the community, especially business actors, especially in Ngrimbi Village, Bareng District, Jombang Regency regarding the importance of business legality and provide assistance in making a business legality. The method of implementing community service carried out by Group 10 KKN-T MBKM UPN "Veteran" East Java is divided into 3 (three) stages, the first step begins with providing understanding to business people about the importance of business legality through socialization that we held in the first week. Second, data collection of all Ngrimbi village Micro, Small and Medium Enterprises (MSMEs) and registering NIB (Business Identification Number) which has been scheduled by the village. The third is business mentoring with the aim of improving and marketing the products they want to sell. The implementation of this activity was carried out by Group 10 KKN-T MBKM UPN "Veteran" East Java consisting of 10 people. The result of this activity is the awareness of business actors in Ngrimbi Village about the importance of business legality for Micro, Small and Medium Enterprises (MSMEs), and as many as 20 MSMEs that have been surveyed by group 10 in Ngrimbi Village, 19 MSMEs have carried out business legality in the form of NIB (Business Identification Number).